EFEK JUS BATANG BROTOWALI (Tinaspora crispa L. Miers) TERHADAP GAMBARAN ERITROSIT, PCV, DAN TPP TIKUS WISTAR (Rattus norvegicus) YANG DIINDUKSI ALOKSAN - , STEPHANI LETICIA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The increasing of financial and the change of lifestyle especially in big city increased the prevalence of degenerative diseases, such as diabetes mellitus. All this time the treatment of diabetes mellitus is using synthetic anti-diabetic drugs, but the production cost of these drugs is relative high. Furthermore the use of synthetic drugs can cause some side effects like permanently damaged organs. Therefore traditional drugs made from nature ingredients that can be made easily are required. Brotowali (Tinaspora crispa L. Miers) is one type of medicinal drug used by Indonesian citizen to treat diabetes mellitus. This research was conducted in 2 phases, first phase is the pre research and the second phase is the research. The aim of the first phase is to determine the right dose of alloxan tetrahydrat to induce diabetes melitus in rats. The aim of second phase is to understand the effect of Brotowali stem juice to erythrocyte (total erythrocyte, hemoglobin concentration MCV, MCH, and MCHC), PCV, and TPP of diabetic rats. First phase of this research used 4 female Wistar rats which were induced intraperitoneally by different dose of alloxan tetrahydrat dissolved with normal saline. First rat was induced three times with alloxan dose 120 mg/kg BW, second rat was induced once with alloxan tetrahydrat dose 150 mg/kg BW, third rat rat was induced once with alloxan tetrahydrat dose 180 mg/kg BW, and forth rat was induced three times with alloxan tetrahydrat dose 150 mg/kg BW. Observations were made of the symptoms of diabetes (polydipsia, polyphagia, and polyuria) and blood glukose was checked at 24 hours, 48 hours, and 72 hours. Second phase if this research used 25 female Wistar rats which were divided into 5 groups and induced three times by alloxan tetrahydrate (150 mg/kg BW) with exception of group V, which was a negative control. Group I was given Brotowali stem juice dose 1 (18 mg/200 g BW of rat), group II and III were given Brotowali stem juice dose 2 (9 mg/200 g BW of rat), group IV as a positive control was given 1 mL of aquades, and group V without injection of alloxan tetrahydrat was given Brotowali stem juice dose 2 (9 mg/200 g BW of rat). Blood sampling was done before alloxan injection (day 0), after administration of Brotowali stem juice (day 16), and at the end of research (day 28). Parameters measured were erythrocyte ((total erythrocyte, hemoglobin concentration MCV, MCH, and MCHC), PCV, and TPP. The result of first phase research showed alloxan tetrahydrat with dose three times 120 mg/kg BW, 150 mg/kg BW, 180 mg/kg BW, and three times 150 mg/kg BW, which dissolved with normal saline cannot induced diabetes mellitus in rats. Alloxan tetrahydrat with dose three times 150 mg/kg BW which dissolved with 0,01 M HCl can induced diabetes mellitus in rats. The result of second phase of this research showed Brotowali stem juice dose 1 (18 m/ 200 g body weight) cannot restore the erythrocyte (total erythrocyte, xv hemoglobin concentration MCV, MCH, and MCHC) PCV and TPP of diabetic rats on day 28 and Brotowali stem juice dose 2 (9 mg/200 g BW) cannot restore the erythrocyte (total erythrocyte, hemoglobin concentration MCV, MCH, and MCHC) but can restore the PCV and TPP of diabetic rats on day 28